Spatial ecology, phenological variability and moulting patterns of the Endangered Atlantic petrel Pterodroma incerta - M Pastor-Prieto; R Ramos; Z Zajková; JM Reyes-González; ML Rivas; PG Ryan; J González-Solís (Endangered Species Research, 2019)
Insights into the year-round movements and behaviour of seabirds are essential to better understand their ecology and to evaluate possible threats at sea. The Atlantic petrel Pterodroma incerta is an Endangered gadfly petrel endemic to the South Atlantic Ocean, with virtually the entire population breeding on Gough Island (Tristan da Cunha archipelago). We describe adult phenology, habitat preferences and at-sea activity patterns for each phenological phase of the annual cycle and refine current knowledge about its distribution, by using light-level geolocators on 13 adults over 1-3 consecutive years. We also ascertained moulting pattern through stable isotope analysis (SIA) of nitrogen and carbon in feathers from 8 carcasses. On average, adults started their post-breeding migration on 25 December, taking 10 d to reach their non-breeding areas on the South American shelf slope. The pre-breeding migration started around 11 April and took 5 d. From phenological data, we found evidence of carry-over effects between successive breeding periods. The year-round distribution generally coincided with the potential distribution obtained from habitat modelling, except during the non-breeding and pre-laying exodus periods, when birds only used the western areas of the South Atlantic. Moulting occurred during the non-breeding period, when birds spent more time on the water, and results from SIA helped us to distinguish feathers grown around Gough Island from those grown in the non-breeding area. Overall, our results bring important new insights into the spatial ecology of this Endangered seabird, which should help improve conservation strategies in the South Atlantic Ocean.